Aerodynamic Performance Improvement on NACA 4415 Airfoil by Using Cavity: Peningkatan Performa Aerodinamika NACA 4415 dengan Menggunakan Cavity - James Julian; Waridho Iskandar; Fitri Wahyuni; Nely Toding Bunga (Fakultas Teknik Universitas Pancasila, 2023)
This study uses a numerical method to analyze the cavity's use on the airfoil's trailing edge and the aerodynamic effects it generates. The type of airfoil used is NACA 4415. The variations in the Reynolds number examined in this study are 2×105 and 3×105. The governing equation is the Reynolds Averaged Navier-Stokes paired with the k-ε turbulence model. This study concludes that the cavity can increase Cl in the airfoil but cannot delay the stall. The increase in Cd is also a negative effect of using a cavity in the airfoil. The cavity can increase Cl by increasing the pressure on the lower side near the trailing edge. Meanwhile, the cavity increases Cd because it creates a separation of the fluid flow, forming a vortex when viewed in a streamlined form of fluid flow.